2021
DOI: 10.1111/ddg.14464
|View full text |Cite
|
Sign up to set email alerts
|

Ocular syphilis – a case series of four patients

Abstract: Summary Ocular manifestations of syphilis with visual impairment symptoms may occur already at the stage of secondary syphilis. They may also be the only manifestation of syphilis and mimic other diseases of the eye. Therefore, in all patients with uveitis, optic neuritis, optic atrophy, acute ocular muscle paresis, or loss of visual acuity, syphilis infection should be ruled out, even if the medical history does not initially raise suspicion. Ocular involvement should be treated as neurosyphilis. Delayed diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
9

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 11 publications
(22 reference statements)
1
11
0
9
Order By: Relevance
“…Previous investigations revealed that ocular syphilis eyes with uveitis showed a good response to penicillin G treatment and better visual improvement than those with optic atrophy and that delay in treatment also indicated poor visual prognosis (3,5,(14)(15)(16). In our study, except ARN, most ocular syphilis with active inflammation responded well to standard penicillin G therapy, no matter what the initial BCVA, ocular disease type, and RPR titers were as long as it was diagnosed early and treated properly.…”
Section: Discussionsupporting
confidence: 52%
“…Previous investigations revealed that ocular syphilis eyes with uveitis showed a good response to penicillin G treatment and better visual improvement than those with optic atrophy and that delay in treatment also indicated poor visual prognosis (3,5,(14)(15)(16). In our study, except ARN, most ocular syphilis with active inflammation responded well to standard penicillin G therapy, no matter what the initial BCVA, ocular disease type, and RPR titers were as long as it was diagnosed early and treated properly.…”
Section: Discussionsupporting
confidence: 52%
“…27 Ocular involvement of syphilis can be observed as early as stage II. 28 The most common clinical manifestation is uveitis. However, any part of the eye can be affected.…”
Section: Other Manifestations Of Syphilis Ocular Syphilismentioning
confidence: 99%
“…27,28 The typical and most common presentation is binocular posterior uveitis or panuveitis. 27,28 Ocular syphilis is significantly more prevalent in men (58-100%) than in women and can affect patients of any age, with an average age in the fifth decade of life. 27 The most common clinical manifestation is uveitis.…”
Section: Other Manifestations Of Syphilis Ocular Syphilismentioning
confidence: 99%
See 2 more Smart Citations